'Lessons learned' during the Interbellum: 'Irish war' and British counterinsurgency. (4th July 2021) - Malkin, Stanislav
ABSTRACT: Historians generally view the Irish War of Independence as the first and largely unsuccessful experience for the British army in conducting modern counterinsurgency. This article argues that during the Interbellum the 'Irish war' became a starting point for the military thought about this type of conflict, although this did not become fully consolidated in the army's thinking. Some important aspects of the British forces' conduct in the 'Irish war' remained undervalued, not least because of the only official analysis of this conflict, 'The Record of the Rebellion in Ireland', was classified for a long time. It strongly challenges traditional and revisionist understanding of this conflict and its implications on the British way of counterinsurgency during the Interbellum. These contradictions between documentary evidence from archives and established methods of historical thinking, as well as correlations of archival material with our understanding of modern counterinsurgencies, will be contrasted and analysed in this article.